Hyperglycaemia induces metabolic dysfunction and glycogen accumulation in pancreatic β-cells - Melissa F. Brereton (Nature Portfolio, 2016)
Diabetes is characterized by prolonged hyperglycaemia and tissue damage in pancreatic islets. Here, Brereton et al. show that chronic high glucose levels lead to glycogen accumulation in β-cells, associated with reduced autophagy, impaired metabolism, insulin granule depletion and apoptosis.